Danger signals – damaged-self recognition across the tree of life - Heil, Martin; Land, Walter G. (Frontiers in Plant Science, 2014)
Multicellular organisms suffer injury and serve as hosts for microorganisms. Therefore, they require mechanisms to detect injury and to distinguish the self from the non-self and the harmless non-self (microbial mutualists and commensals) from the detrimental non-self (pathogens). Danger signals are 'damage-associated molecular patterns' (DAMPs) that are released from the disrupted host tissue or exposed on stressed cells. Seemingly ubiquitous DAMPs are extracellular ATP or extracellular DNA, fragmented cell walls or extracellular matrices, and many other types of delocalized molecules and fragments of macromolecules that are released when pre-existing precursors come into contact with enzymes from which they are separated in the intact cell. Any kind of these DAMPs enable damaged-self recognition, inform the host on tissue disruption, initiate processes aimed at restoring homeostasis, such as sealing the wound, and prepare the adjacent tissues for the perception of invaders. In mammals, antigen-processing and -presenting cells such as dendritic cells mature to immunostimulatory cells after the perception of DAMPs, prime naïve T-cells and elicit a specific adaptive T-/B-cell immune response. We discuss molecules that serve as DAMPs in multiple organisms and their perception by pattern recognition receptors (PRRs). Ca2+- fluxes, membrane depolarization, the liberation of reactive oxygen species (ROS) and mitogen-activated protein kinase (MAPK) signalling cascades are the ubiquitous molecular mechanisms that act downstream of the PRRs in organisms across the tree of life. Damaged-self recognition contains both homologous and analogous elements and is likely to have evolved in all eukaryotic kingdoms, because all organisms found the same solutions for the same problem: damage must be recognized without depending on enemy-derived molecules and responses to the non-self must be directed specifically against detrimental invaders.